Alder-ene reactions driven by high steric strain and bond angle distortion to form benzocyclobutenes - Gupta, Saswata (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
A unique aryne-based Alder-ene reaction to form benzocyclobutene is described. In this process, the thermodynamic barrier to form a four-membered ring is compensated by the relief of the strain energy of an aryne intermediate. On the other hand, the driving force to overcome the high kinetic barrier is provided by the gearing effect of the bulky substituent at the ortho-position of the ene-donor alkene. To maximize the steric strain by the ortho-substituent, a structural element for internal hydrogen bonding is installed, which plays a crucial role for both the hexadehydro Diels–Alder and the Alder-ene reactions. DFT calculations show that the bulky hydrogen bonding element lowers the activation barrier for the Alder-ene reaction by destabilizing the intermediate, which is due to the severe bond angle distortion. The preferred formation of cis-isomers can also be explained by the extent of bond angle distortion.